The Roles of Parent and Teacher on Children Attitude Development to Avoid Bullying Behavior in Early Childhood - Putu Eka Sastrika Ayu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Family takes important influences on the education of children's moral and personality development. Families especially parents are the main agencies to teach children new things as well as goodness or badness. Early family education should include three aspects namely cognitive, affective and psychomotor aspects. In early family education, parents should impart honest behaving, polite speaking, and responsibility-taking. In this early family education, educational interaction occurs firstly and foremost to the children who would become the foundation of their further education. Cultivating children's attitudes should be carried out by school teachers. There are several roles that can be implemented by the teacher namely; as a model, mentor, coach, motivational speaker, and evaluator. The role of teachers as educators (nurturer) are the roles that are associated with the duties of assistance and encouragement (supporter), the tasks of supervision and coaching (supervisor) as well as tasks related to disciplining children the child was being well behaved against the school rules and norms of life in the family and society. By optimizing the role of parents and teachers in the cultivation of the attitude, then it will be able to reduce bullying behavior in early childhood. The children's experiences with bullying will give long term impacts. For the children having bullying victims, the experience will be a nightmare that never disappears from their memories.